Identifikasi Identifikasi Fitokimia Daun Gandarusa (Justicia Gendarussa L.) Asal Kabupaten Pangkep: Analisis Kandungan Senyawa Aktif Menggunakan Metode Kromatografi dan Uji Fitokimia - Ildayani, Ildayani; Ramadhani, Livia Ernesta; Sa’adah, Nur Lailatus; Apriliani, Ayu; Natasya, Natasya; Ikram, Nurul; Mutiara, Sitti Ayzah; Sari, Andi Aliya Meilana; Sahruni, Sahruni; Usman, Fityatun; Haryanto, Haryanto (Prodi Farmasi Fakultas Kedokteran Universitas Hang Tuah, 2024)
Gandarusa leaves (Justicia gendarussa L.) are recognized as medicinal plants rich in various active phytochemicals. Extraction was carried out using the maceration method with 96% ethanol, followed by evaporation with a rotary evaporator to obtain a concentrated extract. Fractionation was performed using liquid-liquid partitioning with n-hexane and ethyl acetate to separate compounds based on polarity. The results revealed the ethyl acetate fraction had the highest yield at 20.8%, followed by the n-hexane fraction at 20%. Phytochemical identification using thin-layer chromatography confirmed the presence of alkaloids, flavonoids, and steroids. UV-Vis spectrophotometry analysis showed the total flavonoid content reached 0.741 mg/L based on the quercetin standard curve. These findings highlight the potential of gandarusa leaves as a promising source of bioactive compounds for pharmaceutical development.